Degradation of Oil Shale by Sulfur-Oxidizing Bacteria - Findley, J. (1974)
Approximately 40% of oil shale can be solubilized by the action of sulfur-oxidizing bacteria. Thiobacillus thiooxidans and Thiobacillus concretivorous are equally effective in solubilization. Continuous leaching experiments show that this process can be completed within 14 days. The growth of Thiobacillus and the production of acid were measured under several conditions. Almost all of the CaMg(CO(3))(2) was removed by this process, leaving a complex of silica and kerogen that could be burned as low-energy fuel. The silica-kerogen complex had not yet been biologically degraded.